Factors that affect the foreign trade performance of regional economic integration organization members—evidence from APEC - Wang, Di (2019)
In recent years, countries are willing to increase production efficiency through international cooperation. Regional economic integration is becoming increasingly popular owing to it helps member states to seek more foreign trade. The dissertation aims to research the determinants that affect the foreign trade performance of regional economic integration organization members by OLS linear regression. Besides, which factor has the most substantial impact on international trade would be estimated. Finally, the regression result shows that regional integration organization, inward FDI, outward FDI, and the exchange rate have a significantly positive correlation with a country’s foreign trade performance, and the exchange rate is the strongest factor.